Success rates of video vs. direct laryngoscopy for endotracheal intubation in anesthesiology residents: a study protocol for a randomized controlled trial (JuniorDoc-VL-Trial) - Uzun, Davut D.; Eicher, Simge; Mohr, Stefan; Weigand, Markus A.; Schmitt, Felix (Trials, 2025)
Tracheal intubation is a core skill in airway management for anesthesiologists as well as for other medical professionals involved in advanced airway procedures. Traditionally, tracheal intubation in hospitals has been performed using a Macintosh blade for direct laryngoscopy (DL). However, recent literature increasingly supports the potential benefits of routine video laryngoscopy (VL). The aim of this study was to assess whether primary training in hyperangulated VL improves the first-pass success rate of tracheal intubation among first-year anesthesiology residents, compared to conventional DL training, in the operating room.